Problematika Peraturan Mahkamah Konstitusi dan Implikasinya - Adam Ilyas; Dicky Eko Prasetio (Jurnal Konstitusi, 2022)
The position of the Constitutional Court Regulation (PMK) in the hierarchy of laws and regulations is not strictly regulated, so it is not known where it is located, or which institution has the right to conduct a judicial review of it. Therefore, this study will examine three things, namely: (i) the position of PMK; (ii) the implications of PMK that have not been promulgated; and (iii) the institution entitled to conduct a judicial review of PMK. The research method used is the normative legal research method. The result is that PMK has a "conditional" position equivalent to a presidential regulation because it has the same function. Despite having the same "conditional" position, the PMK has so far not been able to be tested by any institution because it has not been promulgated in the State Gazette, which should also imply that it cannot bind the public. Therefore, PMK should be promulgated in the State Gazette to bind the public, and the institution entitled to examine it is the Supreme Court. That way, the parties to the proceedings at the Constitutional Court will obtain legal certainty and protection.